Analisis Waktu dan Biaya Perbandingan Erection Box Girder Menggunakan Metode Crane dan Launcher - Bunga Islami Fortuna; I Ketut Sucita; Rikki Sofyan Rizal (Jurnal Ilmiah Rekayasa Sipil, 2021)
The most important thing in the construction of toll roads, especially elevated toll roads, is the erection girder. The implementation of this erection girder certainly requires a long time and a large cost, so it requires the right work method in its implementation. The construction of the X Section A Toll Road Project is the construction of an elevated toll road where its implementation is limited by time and cost so that it requires the right work method to achieve timely and cost-efficient project completion. The girder used in this project is a box girder with the implementation method using the crane and launcher method. This study aims to analyze the time and cost of comparing the implementation method of erection box girder using cranes and launchers to obtain a more efficient and effective implementation method. This research was conducted through field observations to observe the erection box girder time and collect secondary data regarding the method of implementing erection box girder. The analysis carried out in this study includes time calculation analysis by calculating the average time value of the erection box girder implementation using statistical formulas and cost analysis carried out by referring to the PUPR Ministerial Regulation Number 28/PRT/M/2016 concerning Analysis of Unit Prices for Public Work. Based on the outcomes of the calculation of time and cost analysis, the duration of the erection box girder with the crane method is 70.65 minutes and requires a cost of Rp 23,769,579 and the launcher method takes 48.12 minutes and costs Rp 11,834,500. Thus, it can be seen that the more efficient and effective erection box girder method is the launcher method with a cost difference of Rp 11935,079 and 32% efficiency. when compared to the crane method.